Historia y clima - Nomberto Bazán, Víctor Raúl (2020)
This article analyzes climate change from a historical perspective. Therefore, it begins with a summary of the background and evolution of the approach taken by academics and authorities in this regard. All of that is framed within the challenges presented in order to face the consequences that global warming will bring to the human population, especially in the Peruvian case. With that purpose, it puts emphasis on the most urgent aspects and the proposals made about the problem. Finally, it discusses the measures taken during the meetings conducted by different countries and international organizations in order to generate compromises which allow the viability of reducing climate change and its effects.